Aspektualitaet im Polnischen und Deutschen Eine praktische Untersuchung am Beispiel der Uebersetzungen beider Richtungen - Gulawska, Malgorzata (Slavistische Beitraege, 2000)
The author of this thesis is aware that the above-mentioned contrastive studies deal extensively with the aspect and action type issues from their respective perspectives. Nevertheless, she has decided to take a stand on this topic herself. 1. The essay is a Germanic work that represents certain areas of the German language in contrast to Polish. 2. The aim of the work is a linguistic text analysis and not the description of the language systems. For the purposes of the essay, various texts have been selected and analyzed and described according to certain principles. Therefore, the results of the study are text corpus related. 3. The broad definition of aspectuality enables the comparison of different phenomena that are not only related to the verbal level but also take into account the contextual sentence and text levels. 4. Both translation directions Polish-German and German-Polish will be considered in the paper. Not only Polish, but also German original texts provide pertinent signals that need to be described and that can usually be found again in the translation.